(untitled) (Archives of Clinical and Medical Case Reports, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a rare and severe condition of immune dysregulation characterized by severe organ damage induced by a hyperinflammatory response and uncontrolled T-cell and macrophage activation. Secondary HLH, also known as macrophage activation syndrome, commonly presents in adulthood and characterized by acquired immune dysfunction in response to infections, malignancies, or autoinflammatory/autoimmune disorders. Secondary HLH induced by regorafenib has not been yet described. Here we report a case of HLH induced by regorafenib, confirmed by clinical, laboratory and histopathological findings, with typical results on bone marrow aspiration.